The Power of Death-Cast in They Both Die at the End by Adam Silvera: A Hegemony Analysis - NFN Masnuah; Erika Citra Sari Hartanto (Balai Bahasa Kalimantan Tengah, 2022)
This study discusses the issue of power in the novel They Both Die at the End by Adam Silvera analyzed using the hegemony theory by Antonio Gramsci. The focus of this study is Death-Cast power over other groups that have a lower position in the novel. This study aimed to find out the dominant and the subordinate group in the novel. This study used a qualitative design with a close-reading method. Data collection was done by reading the novel repeatedly, marking the parts in the novel that were in accordance with the research objectives using Antonio Gramsci's theory, and taking notes. Data analysis was carried out in three steps, such as data reduction, data display, and conclusion. The result of this study showed that power inequality in the novel can cause the presence of the dominant group and the subordinate group. The dominant group in the novel is Death-Cast which is a part of civil society. The subordinate group in the novel is Decker, President, and the herald.AbstrakPenelitian ini membahas persoalan kekuasaan dalam novel They Both Die at the End karya Adam Silvera yang dianalisis menggunakan teori hegemoni Antonio Gramsci. Fokus penelitian ini adalah kekuatan Death-Cast atas kelompok lain yang memiliki posisi lebih rendah dalam novel. Penelitian ini bertujuan mengetahui kelompok dominan dan kelompok bawah dalam novel. Penelitian ini menggunakan desain kualitatif dengan metode close-reading. Pengumpulan data dilakukan dengan membaca novel secara berulang-ulang, menandai bagian-bagian dalam novel yang sesuai dengan tujuan penelitian menggunakan teori Gramsci, dan mencatat. Analisis data dilakukan dalam tiga tahap, yaitu reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa ketimpangan kekuasaan dapat menyebabkan hadirnya kelompok dominan dan kelompok subordinat. Kelompok dominan dalam novel tersebut adalah Death-Cast yang merupakan bagian dari “masyarakat sipil”. Kelompok bawahan dalam novel tersebut adalah Decker, President, dan herald.